The significance of Good Chair as part of children's school and home environment in the preventive treatment of body statistics distortions - Mirosław Mrozkowiak; Hanna Żukowska (Kazimierz Wielki University, 2015)
Mrozkowiak Mirosław, Żukowska Hanna. Znaczenie Dobrego Krzesła, jako elementu szkolnego i domowego środowiska ucznia, w profilaktyce zaburzeń statyki postawy ciała = The significance of Good Chair as part of children's school and home environment in the preventive treatment of body statistics distortions. Journal of Education, Health and Sport. 2015;5(7):179-215. ISSN 2391-8306. DOI 10.5281/zenodo.19832 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A179-215 https://pbn.nauka.gov.pl/works/582700 http://dx.doi.org/10.5281/zenodo.19832 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015.   Znaczenie Dobrego Krzesła, jako elementu szkolnego i domowego środowiska ucznia, w profilaktyce zaburzeń statyki postawy ciała The significance of Good Chair as part of children's school and home environment in the preventive treatment of body statistics distortions   1Mirosław Mrozkowiak, 1Hanna Żukowska   1Uniwersytet Kazimierza Wielkiego, Instytut Kultury Fizycznej 1Kazimierz Wielki University, Physical Culture Institute     Słowa kluczowe: Dobre Krzesło, przestrzenne asymetrie postawy ciała. Key words: Good Chair, spatial asymmetries of body posture.   Streszczenie   Wstęp W wieku od 7 do 12 lat występuje zdecydowanie największy odsetek postaw o zaburzonej symetrii przestrzennej, a ósmy rok życia jest okresem, w którym występuje szczególne zagrożenie prawidłowej postawy ciała. Analiza zebranych wyników pod kątem częstości występowania różnych zaburzeń postawy wykazała, że najczęstszy błędem postawy ciała wśród dzieci i młodzieży polskiej jest postawa o asymetrycznym przebiegu linii wyrostków kolczystych kręgosłupa wypukłością skierowaną w lewo 23,81% i cechach pleców okrągłych 17,34%. Środowisko szkolne i domowe ucznia to między innymi meble, które nie tylko powinny harmonizować z otaczającą przestrzenią, być estetyczne i praktyczne, adekwatne do masy i wysokości ciała, ale również komfortowe dla dziecka. Oznacza to, że kryteria ich doboru muszą brać pod uwagę wymogi ergonomii: dostosowanie do długości i rodzaju wykonywanej aktywności, jego proporcje uwzględniające masę i wysokość ciała, aktywność fizyczną podczas lekcji i przerw międzylekcyjnych. Celem badań było określenie w jakim stopniu Dobre Krzesło, jako element środowiska szkolnego i domowego ucznia, oddziałuje na zaburzenia statyki postawy ciała w wieku od 7 do 10 lat. Materiał i metoda Materiał badawczy stanowiło w 1 edycji: 194, drugiej: 194 i 3 edycji 142 dzieci  Szkół Podstawowych, w których trzykrotnie przestrzennie zdiagnozowano postawę ciała, stosując zestaw komputerowy wykorzystujący zjawisko mory projekcyjnej. Dzieci podzielono na trzy grupy, te które korzystały z Dobrego Krzesła w szkole i w domu, które korzystały z Dobrego Krzesła tylko w szkole i te które korzystały z krzeseł tradycyjnych w szkole i domu. Wnioski   • Dobre Krzesło w procesie korekcji zaburzeń statyki ciała pełni istotną i uzupełniającą rolę w stosunku do wysiłków fizycznych stosowanych w ramach zajęć korekcyjnych postawy ciała. Jest rodzajem ortezy, spełniającej zadania pomocniczego sprzętu ortopedycznego w profilaktyce dzieci w wieku 7-10 lat. • Podjęty problem wymaga szeroko zakrojonych badań środowiska szkolnego i jego oddziaływania na postawę ciała ucznia. Program diagnozujący znaczenie różnych zagrożeń somatyki należy wdrożyć niezwłocznie, bowiem planowana reforma edukacji wprowadza do szkoły dzieci sześcioletnie.   Summary   Introduction In children and teenagers at the ages from 7 to 12 one observes the highest percentage of distorted body posture symmetry, and the children at the age of 8 are especially prone to possible body posture distortions. Research on the frequency of incidence of various body posture distortions indicates that the most common reason of poor body posture among Polish children and adolescents is asymmetrical spinous process protruding left, in 23,81% of the individuals, and hyperkyphosis (round back), in 17,34% of the individuals.  Children's school and home environment comprises inter alia of the furniture, which should not only harmonize with surrounding space but also be aesthetically pleasing and practical, proportional to children's body mass and height as well as comfortable. Therefore the criteria of furniture choice need to remain in agreement with some ergonomic requirements, namely they should be adjusted to the duration and kind of performed activity, proportional to children's body mass and height as well as children's physical activity during lessons and interclass breaks. The aim of the study was to determine to what extent Good Chair as part of school and home environments affects body statistics distortions at the ages from 7 to 10.   Materials and methods Research material in first edition of the study was collected from 194 primary school children, in second edition from 194 primary school children and in the third edition from 142 primary school children, whose body posture was analyzed three times with the use of a computer set with projection moiré. The children were divided into three groups, those who used Good Chair at school and at home, those who used Good Chair only at school and those who used traditional chairs at school and at home.   Conclusions • Good Chair plays a significant role, and complementary to physical effort performed during corrective classes, in the correction of body statistics distortions. It is a kind of orthotics, being a supplementary orthopedic equipment in the preventive treatment of children at the ages from 7 to 10. • The problem undertaken in the study requires broad research on the school environment and its effects on children's body posture. Diagnostic research into various threats to body somatics should be implemented immediately, especially because the planned education reform introduces the six-year-olds to schools.